The impact of socially responsible HRM practices on nurse performance - Houri, Maya; Chaarani, Hani EL; Beydoun, Abdul Rahman (Nurture, 2024)
Purpose: This paper investigates the impact of socially responsible human resource management practices on nurses’ performance in Lebanon’s healthcare sectors. It examines how certain HRM practices, namely training, compensation, performance evaluation, work-family balance and occupational health and safety affect nurses’ performance. Design/Methodology/Approach: Survey data was collected from 389 public and private sector nurses. Structural equation modeling was used for analysis. Findings: The results show a positive impact of socially responsible human resources management practices, namely training, compensation, and occupational health and safety on nurses’ performance. Conclusion: The findings draw attention to the important role played by SRHRM in evoking nurses’ performance. Research Implications: At the academic level, it provides supplementary literature for the under-researched sector in Lebanon. It might thus open up additional research opportunities that aim to broaden the perspective of the topic. At the practical level, the findings offer hospitals the tools to be competitive in retaining nurses. It is also expected to aid policymakers and HR practitioners with means to ensure a better quality of service is provided for the patients. Originality and Value: This research might be considered the first to investigate the mentioned topic.